Factors Influencing Fintech Adoption Among MSME’s in Bandung West Java Indonesia - Jimmy Julio Ratu Edo; Abdul Mukti Soma; Palti Marulitua Sitorus (JASF: Journal of Accounting and Strategic Finance, 2024)
The purpose of this study was to identify and quantify the factors impacting the adoption of fintech by micro, small, and medium-sized enterprises (MSMEs) in Bandung. The factors are perceived ease of use, perceived utility, financial literacy, user innovation, government assistance, and trust. Based on the data gathered, this study comprised 356 participants who are either performers or owners of Micro, Small, and Medium Enterprises (MSMEs) in Bandung. The correlation between variables is investigated in this study utilising the Partial Least Squares (PLS) data analysis approaches and SmartPLS v 3.2.9 software. The results of the study show that perceived simplicity of use, perceived usefulness, user innovativeness, and trust all have a major impact on Fintech acceptance. In contrast, financial literacy and government backing have no substantial impact on fintech uptake. This study emphasizes the importance of fintech service providers to prioritize ease of service and build trust..Then the government ought to accelerate the development of information and communication technology (ICT) infrastructure, such as expanding mobile broadband coverage and promoting Fintech companies through advantageous laws. Incorporating financial literacy into the school curriculum may help to reduce information asymmetry and improve financial accessibility, hence promoting the growth of MSMEs.